Pregnancy outcomes in DMARD-exposed patients with juvenile idiopathic arthritis—results from a JIA biologic registry. (14th August 2019) - Drechsel, Paula; Stüdemann, Katrin; Niewerth, Martina; Horneff, Gerd; Fischer-Betz, Rebecca; Seipelt, Eva; Spähtling-Mestekemper, Susanna; Aries, Peer; Zink, Angela; Klotsche, Jens; Minden, Kirsten
Abstract: Objectives: To investigate the courses and outcomes of pregnancies involving JIA patients who were exposed to DMARDs. Methods: In the Juvenile arthritis MTX/Biologics long-term Observation study, pregnant patients or male patients with pregnant partners were identified. Standardized patient interviews were conducted, and the course and outcome of pregnancy were assessed. Prospectively collected physician- and patient-reported data were also considered in the analysis. Results: The study sample included 152 pregnancies in 98 women with JIA and 39 pregnancies involving 21 male patients as partners. The majority of patients had polyarticular-onset/-course JIA (61%). The average age of patients at first pregnancy was 24.1 (4.5) years, and their mean disease duration was 13.8 (5.9) years. Patients had been exposed to DMARDs for 9.5 (5.6) years, and 90% of these patients had received biologics before. Half of the pregnancies occurred during DMARD exposure, mostly with etanercept. Significant differences in pregnancy outcomes between DMARD-exposed and -unexposed pregnancies were not observed. Spontaneous abortion (13.1%) and congenital anomaly (3.6%) rates were not suggestive of increased risk compared with expected background rates. However, the rates of premature birth (12.3%) and caesarean section (37.7%) were slightly above those in the German birthing population. The disease activity of female patients remained relatively stable in pregnancy, with mean cJADAS-10 scores of 5.3, 7.1 and 5.6 in each trimester, respectively. Conclusion: Young adults with JIA often become pregnant or become fathers of children while still being treated with DMARDs. Data suggest no increased risk of major adverse pregnancy outcomes.